Protocol for isolation and ATAC-seq library construction of zebrafish red blood cells - Yanyan Ding; Feng Liu (STAR Protocols, 2022)
Summary: Understanding chromatin dynamics in red blood cells (RBCs) is critical for exploring the differentiation process and homeostasis maintenance during erythropoiesis. Here, we describe a protocol for isolation of zebrafish erythrocytes labelled with gata1:dsRed by fluorescence-activated cell sorting. We detail steps for ATAC-seq library construction from the isolated RBCs and describe how to analyze the quality of the library. The library can then be used to assay genome-wide chromatin accessibility in these RBCs.For complete details on the use and execution of this protocol, please refer to Ding et al. (2021).1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.